Global nutrition report 2015: Africa brief: Actions and accountability to advance nutrition and sustainable development - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As we move into the post-2015 era of the Sustainable Development Goals (SDGs), the world faces many seemingly intractable problems. Malnutrition should not be one of them. The incentives to improve nutrition are strong, and determined countries can make rapid advances in malnutrition reduction. Good nutrition provides a vital foundation for human development that is central to meeting our full potential. When nutrition status improves, it leads to a host of positive outcomes for individuals and families. Improved nutrition worldwide means many more children will live past the age of five, their growth will be less disrupted, and they will gain in height and weight. Their cognitive abilities will develop more fully, allowing them to learn more both within and outside of school. As a result of sufficient nourishment and a positive early environment, children are more likely to get better jobs and fewer illnesses as adults—aging healthily and living longer.